sFlt-1/PlGF ratio for the predictive diagnosis of preeclampsia: budget impact analysis from the public healthcare perspective in Portugal - Campos,Ana (2019)
Overview and Aims: The last decade brought relevant insights into the pathophysiology of preeclampsia (PE), namely the role of the circulating levels of placental growth factor (PlGF) and soluble Fms-like tyrosine kinase-1 (sFlt-1). The purpose of this study is to estimate the financial impact of introducing the sFlt-1/PlGF ratio for the evaluation of women with suspicion of PE in the Portuguese National Healthcare System (SNS). Study Design: budget impact study evaluating short-term costs associated with the introduction of the sFlt-1/PlGF ratio from the SNS payer's perspective. The time horizon for the study is 1 year. Population: The target population consists of women presenting to the healthcare system with signs or symptoms suggestive of preeclampsia (estimated in 8500 subjects). Methods: A decision-tree model was used to estimate the budget impact of the introduction of the sFlt-1/PlGF ratio in the SNS. The model compares the management costs in the current clinical practice (no test scenario) vs. current diagnostic procedures plus the sFlt-1/PlGF ratio (test scenario). Clinical inputs have been derived primarily from literature review and, where data was unavailable, expert opinion. Resources and unit costs have been obtained from Portugal-specific sources. Results: In the current standard practice (no test), total costs were estimated to be e9 863 264 (e1160 per patient), with unnecessary admissions representing about e3,5 million. Total costs in the test scenario sum up to e9 781 194 (e1150 per patient), representing a cost saving to the system of e82 070 (e10 per patient), mainly due to a reduction of false positives and related unnecessary hospitalizations of women not developing PE. Conclusions: There is favorable economic evidence about the introduction of the sFlt- 1/PlGF ratio in the SNS. The generated savings appear to offset the costs related to the test.